Effects of ambient PM1 air pollution on daily emergency hospital visits in China: an epidemiological study. Issue 6 (September 2017) - Chen, Gongbo; Li, Shanshan; Zhang, Yongming; Zhang, Wenyi; Li, Daowei; Wei, Xuemei; He, Yong; Bell, Michelle L; Williams, Gail; Marks, Guy B; Jalaludin, Bin; Abramson, Michael J; et al.
Summary: Background: China is experiencing severe ambient air pollution. However, few studies anywhere have examined the health effects of PM1 (particulate matter with aerodynamic diameter <1 μm), which are a major part of PM2·5 (particulate matter with aerodynamic diameter <2·5 μm) and even potentially more harmful than PM2·5 . We aimed to estimate the effects of ambient daily PM1 and PM2·5 concentrations on emergency hospital visits in China. Methods: In this epidemiological study, we collected daily counts of emergency hospital visits from the 28 largest hospitals in 26 Chinese cities from Sept 9, 2013, to Dec 31, 2014. Ground-based monitoring data for PM1 and PM2·5 and meteorological data were also collected. Hospital-specific emergency hospital visits associated with PM1 or PM2·5 were evaluated with a time-series Poisson regression. The effect estimates were then pooled at the country level using a random-effects meta-analysis. Findings: The mean daily concentration of PM1 in all cities was 42·5 μg/m 3 (SD 34·6) and of PM2·5 was 51·9 μg/m 3 (41·5). The mean daily number of emergency hospital visits in all hospitals was 278 (SD 173). PM1 and PM2·5 concentrations were significantly associated with an increased risk of emergency hospital visits at lag 0–2 days (cumulative relative risk [RRs] 1·011 [95% CI 1·006–1·017] for a 10 μg/m 3 increase in PM1 and 1·010 [1·005–1·016] for a 10 μg/m 3 increase in PM2·5 ). Slightly higher RRs of ambient PM1 and PM2·5 pollution were noted among women and children than among men and adults, respectively, but without statistical significance. Given a cause-effect association, 4·47% (95% CI 2·05–6·79) and 5·05% (2·23–7·75) of daily emergency hospital visits in China could be attributed to ambient PM1 and PM2·5 pollution, respectively. Interpretation: Exposure to both ambient PM1 and PM2·5 were significantly associated with increased emergency hospital visits. The results suggest that most of the health effects of PM2·5 come from PM1 . Funding: None.